Domínio de língua inglesa como fator de mobilidade social na cidade do Salvador - Piauhy, Katiane Andrade Nascimento (2009)
Over the past years, knowledge of the English language has become an important element in the qualification for work in all areas, enabling people to take part in commercial, financial and diplomatic routines without interpreters or translators. This reality has also been affecting the use of the language in the city of Salvador, where the communicative ability in English has been increasingly wished by individuals throughout the process of academic formation. Thus, the knowledge of the language became an element of social inclusion and exclusion in the city of Salvador after international companies came to the state of Bahia and English turned out to be dominant in international organizations. These facts have promoted the emergence of new English schools in the city. For this reason, the present work aims to answer the following question: what is the meaning of the English language knowledge for the social mobility in the city of Salvador? Due to this questioning, the general objective of the study is to verify the meaning of the knowledge of English for the social mobility, inclusion and exclusion in Salvador. More specifically, it aims to: understand the diffusion and knowledge of the language in the socio-economical, political and cultural aspects; understand the social implications of the knowledge of English for the socialization, social exclusion, inclusion and mobility; analyze the diffusion of the English language in Salvador; analyze the knowledge of the English language as an element of social inclusion, exclusion and mobility in Salvador. In order to achieve these goals, the study adopts a methodological strategy that is divided in two steps: a theoretical approach and an empirical study. The theoretical approach comprehends the diffusion and dominance of English in socio-economical, political and cultural terms, and the social implications of this dominance for the socialization, social exclusion, inclusion and mobility. In terms of the empirical study, it analyzes: the diffusion of English language, and the social mobility that comes with its knowledge in Salvador; using the case study technique, which aims to analyze the social mobility presented by students and former students from Associação Cultural Brasil Estados Unidos, ACBEU. The data collected during the case study showed that the majority of the students at the institution is really young and comes from upper classes, that is, the students are already socially included. During the interviews with scholarship students and former students, it was verified that they also consider the learning of English a factor of social inclusion and mobility.